(untitled) (FULafia Journal of Science and Technology, 2026)
Sesame is an important oilseed crop in tropical and subtropical regions; however, its productivity in Nigeria remains low due to the limited availability of improved, high-yielding varieties. The lack of comprehensive information on genetic variability for both agronomic and quality traits hinders effective selection and breeding strategies. Therefore, this study evaluated genetic variability and trait association among agronomic and seed oil-related traits in sesame genotypes to identify selection criteria for yield and quality improvement. Twenty sesame genotypes were evaluated in Lafia LGA of Nasarawa, Nigeria using a randomized complete block design (RCBD) with three replications. Data were collected on agronomic traits, including plant height, number of capsules, number of seeds per capsule and dry seeds weight, as well as seed quality traits such as moisture content, ash content, crude proteins and percentage fat. Analysis of variance revealed significant differences among genotypes for most traits. Principal component (PC1) explained 40% of the variation followed by principal component (PC2) explained 15% of the variation. Dry seed weight contributes indirectly through PC3 (33%) while percentage moisture content through PC4 contributes 12%. Traits such as number of capsules, plant height, and 1000 seed weight contributed significantly to PC1, making them ideal for yield-based selection. Number of capsules per plant, a key yield determinant, showed a positive correlation with crude protein (r=0.36) and fat content (r=0.29). This paper provided useful genotypes which would be serving parents. These parental genotypes could be used in sesame breeding program to develop desirable varieties in Nigeria.